Game Theory Approch on The Decision Making Process for Defining Obtainable Prices At Generator Side in A Deregulated Environment - Modi, A.I; RABARI, T.V (International Journal of Computer Sciences and Engineering, 2018)
For a Deregulated system we assume all Pool participants use a price curve, rather than a cost curve, to exchange the power. Participants think about market prices for which they can maximize their profit, while Pool coordinators try to maximize the system-wide benefits. Using constrained economic dispatch, Pool benefits will be maximized when all participants trade THE power at marginal cost, as participants try to maximize their own benefits, they may either decrease their bids in order to retail more power or increase the price in order to make more profit.